INVESTIGATION OF DRYING PARAMETERS OF BROCCOLİ DURING FAN-ASSİSTED MİCROWAVE, AİR AND A COMBİNED MİCROWAVE/AIR DRYING - S. Karaaslan (Journal of Animal and Plant Sciences, 2016)
Broccoli samples (brassica oleracea), with a moisture of 88.5% (w.b) were dried using three drying methods: fan-assisted microwave, combined microwave-air and air. Drying of broccoli samples continued until moisture decreased to 10% (w.b). Five different microwave powers, 180, 360, 540, 720 and 900 W, were used in microwave drying experiments. The combined microwave-air drying, in which microwave and air drying were applied together, was nine different combination levels. Three different air temperatures 100, 150 and 200 °C, were used in air drying experiments. Periods of drying experiments lasted for 52-13, 35-14 and 125-57 min for microwave, combined microwave-air and air drying, respectively.  Drying characteristics of broccoli were determined and moisture content at any time of drying process was investigated by different drying models. These data were then applied to the thin layer drying models of Newton, Page, Henderson and Pabis, Logarithmic, Midilli-Küçük, Wang and Singh, Logistic, Two Term, Verma, Two Term exponential and Diffusion Approach for determination of the best suitable mathematical models. It was found that the Midilli-Kucuk model described the drying ratio satisfactorily in all drying methods.
Keywords: Broccoli; drying time; drying ratio; mathematical models